2017
DOI: 10.1007/s00228-017-2287-2
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of psychopharmacological prescriptions to clinical practice guidelines in patients with eating behavior disorders

Abstract: CPG adherence was low in EDU-admitted patients. Long-term follow-up showed that clinical outcomes were better and medication costs lower in patients with versus without CPG-adherent prescriptions, likely influenced by the apparently greater severity of illness in those with non-CPG-adherent prescriptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Our data tend to show that although the above may be considered a more than desirable objective for ED specialist care, a rapid and efficient referral to specialist ED care is probably a result we still have to achieve, at least under routine clinical practice conditions in Italy. However, our data are in line with the recent international observations concerning the lack of dissemination, the unsatisfactory implementation, and the low adherence to the recommendations provided by major international guidelines for EDs in clinical practice (Hilbert, Hoek, & Schmidt, ; AlañónPardo, Ferrit Martín, Calleja Hernández, & MorillasMárquez, ).…”
Section: Discussionsupporting
confidence: 90%
“…Our data tend to show that although the above may be considered a more than desirable objective for ED specialist care, a rapid and efficient referral to specialist ED care is probably a result we still have to achieve, at least under routine clinical practice conditions in Italy. However, our data are in line with the recent international observations concerning the lack of dissemination, the unsatisfactory implementation, and the low adherence to the recommendations provided by major international guidelines for EDs in clinical practice (Hilbert, Hoek, & Schmidt, ; AlañónPardo, Ferrit Martín, Calleja Hernández, & MorillasMárquez, ).…”
Section: Discussionsupporting
confidence: 90%
“…Several previous studies have found that ED patients show nonadherence to treatment or routine medical checkups. Therefore, the nonadherence could result in a delay in the early detection or treatment of cancers (Alanon Pardo, Ferrit Martin, Calleja Hernandez, & Morillas Marquez, 2017; Gatt et al, 2014). Several studies have shown that the patients with ED are at the risk of alcohol usage disorder, which in turn is associated with the risk of esophageal, stomach, or even other site cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Also, dangerous drugs such as bupropion or tricyclics, are still prescribed despite the conclusions of the literature [7]. The same observation has been made in other studies on adults and adolescents in different countries [7,8,192]. These papers highlight the disparity between research conclusions and clinical practice in the treatment of AN.…”
Section: Discussionmentioning
confidence: 87%
“…In 2011 the World Federation of Societies of Biological Psychiatry (WFSBP) guidelines for the pharmacological treatment of eating disorders [6] concluded that the majority of the drugs to treat AN are used off-label [6]. These drugs are widely prescribed, but not in compliance with international guidelines [7,8], and can therefore be potentially unsafe for patients with AN.…”
Section: Introductionmentioning
confidence: 99%